TOURISM INDUSTRY OF JAMMU & KASHMIR – CHALLENGES AND OPPORTUNITIES - Shabir Ahmad Lone; Dr. E.Ravi (International Journal of Economic, Business, Accounting, Agriculture Management and Sharia Administration (IJEBAS), 2023)
ABSTRACT Almost every economy in the world relies on tourism to generate cash, create job opportunities, and contribute to the economy's GDP. Tourism is also playing a significant role in the overall development of the state's economy in Jammu and Kashmir. Kashmir has been aptly termed as "Heaven on Earth" for its breathtaking beauty all over the world. Tourism has a lot of promise in Kashmir, and it also gives a lot of commercial chances for residents in the region. This paper looks at the potential, prospects, and constraints of the tourist industry in Jammu & Kashmir.